Lessons Learned From the Clinical Presentation of Common Variable Immunodeficiency Disorders: A Systematic Review and Meta-Analysis - Janssen, Lisanne M. A.; van der Flier, Michiel; de Vries, Esther (Frontiers in Immunology, 2021)
Background Diagnostic delay in common variable immunodeficiency disorders (CVID) is considerable. There is no generally accepted symptom-recognition framework for its early detection. Objective To systematically review all existing data on the clinical presentation of CVID. Methods PubMed, EMBASE and Cochrane were searched for cohort studies, published January/1999-December/2019, detailing the clinical manifestations before, at and after the CVID-diagnosis. Results In 51 studies (n=8521 patients) 134 presenting and 270 total clinical manifestations were identified. Recurrent upper and/or lower respiratory infections were present at diagnosis in 75%. Many patients had suffered severe bacterial infections (osteomyelitis 4%, meningitis 6%, septicemia 8%, mastoiditis 8%). Bronchiectasis (28%), lymphadenopathy (27%), splenomegaly (13%), inflammatory bowel disease (11%), autoimmune cytopenia (10%) and idiopathic thrombocytopenia (6%) were also frequently reported. A bimodal sex distribution was found, with male predominance in children (62%) and female predominance in adults (58%). 25% of CVID-patients developed other manifestations besides infections in childhood, this percentage was much higher in adults (62%). Immune-dysregulation features, such as granulomatous-lymphocytic interstitial lung disease and inflammatory bowel disease, were more prominent in adults. Conclusions The shift from male predominance in childhood to female predominance in adults suggests differences in genetic and environmental etiology in CVID and has consequences for pathophysiologic studies. We confirm the high frequency of respiratory infections at presentation, but also show a high incidence of severe bacterial infections such as sepsis and meningitis, and immune dysregulation features including lymphoproliferative, gastrointestinal and autoimmune manifestations. Early detection of CVID may be improved by screening for antibody deficiency in patients with these manifestations.